Pembiayaan Pendidikan dan Kualitas Pendidikan di SMK Swasta Methodist Tanjung Morawa - Kisno; Sumaryanto; Darwin (Universitas Pancasakti Tegal, 2021)
The purpose of this research was to measure the extent to which the influence of education financing on the quality ofeducation at the Methodist Vocational School of Tanjung Morawa. The respondents of this study were all teachers and the ata were collected through a questionnaire with a Likert scale. The data then were tested and analyzed with the Ms. Excel 2019 and simple linear regression was implemented to analyze the data. The results showed that education financing influenced 63% on the quality of education and the calculated Fvalue was 0.0006 or less than the alpha value = 0.05 which indicated that there was an effect of financing on education on the education quality at the Methodist Tanjung Morawa Vocational School. The regression equation Y = 3.41 + 0.74x, indicated that there was a positive influence of the education financing variable on the education quality variable and the results of the ttest using a significance level of 0.05, the Pvalue obtained was lessr than 0.05 indicating the influence of education financing on the quality of education in Methodist Vocational School of Tanjung Morawa.